Application of the hypercube model with queue priorities and more than one preferential server: A case study on a SAMU - Beojone, Caio Vitor [UNESP]; De Souza, Regiane Máximo [UNESP] (FapUNIFESP (SciELO), 2017)
The study of EMS aims to find ways to provide effective health services and improve the quality of life of the population while respecting the limitations of available resources. In this context, this paper aims to show the potential of application of the hypercube queueing model using queue priorities with more than one preferential server without using partial backup on SAMU, where the workload is relatively low. To do so, were done some experiments with the hypercube queueing model and future scenario prospection by a case study on the SAMU system from Bauru, Brazil. It was evaluated the impacts of demand increase over the system and the acquisition of a new ambulance was evaluated considering the best options to locate it. Main results show that a 50% demand increase can double mean response times. In contrast, minor increases have a smaller impact over the system, as observed on 5.71% and 13.57% demand increases, where the mean response times raised 5% and 16% respectively. The acquisition of a new ambulance was evaluated in terms of mean response times also. The best location had a 3% lower mean response time, on average.
Keywords: Emergency medical systems; Hypercube model; Or in health care; Queueing theory; SAMU